A descarbonização e a importância do gás natural como fonte de energia no processo de transição energética - Otoni, Larissa Pires (Universidade Federal de São Carlos, 2023)
In a scenario of extreme weather conditions and increasingly frequent natural disasters, concern for environmental issues has been gaining more prominence in political, social, and economic discussions. Global warming, one of the central topics in these discussions, is mostly exacerbated by the steadily increasing emission of carbon dioxide (CO2) into the atmosphere, along with other greenhouse gases (GHGs). A significant portion of this emitted CO2 comes from energy generation, with the majority still originating from non-renewable sources. In this context, discussions about energy transition and decarbonization stand out, as we seek a balance between accessibility, reliability, and sustainability. The development and investment in renewable sources take center stage in an ideal energy transition context. However, adapting the infrastructure to accommodate this type of generation in a way that meets global demand can be a time-consuming process, impacting the reduction of carbon dioxide emissions in the coming years and, consequently, definitively influencing long-term outcomes. Therefore, natural gas generation emerges as a short-term ally in emission reduction. When compared to other fossil fuels, natural gas boasts a significant environmental advantage: a 20 to 23% reduction in CO2 emissions from fuel oils and 40 to 50% reduction from solid fuels like coal. Despite its advantages over other fossil fuels, natural gas remains a non-renewable source and significantly contributes to CO2 emissions. For these reasons, its usage should be emphasized as a transitional energy source towards other renewables such as biomass or hydrogen. Therefore, the objective of this undergraduate work is to conduct a literature review addressing the aspects that lead to the utilization of natural gas as a means of transitioning to global adaptation in energy generation through renewable sources.
Decarbonization and the importance of natural gas as an energy source in the energy transition process
Keywords: Descarbonização; Transição energética; Gás natural; Decarbonization; Energy transition; Natural gas; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA